Surrogates of Recognition. On the Reconstruction of a Possible Critical Hegelian Contribution to Current Discussions on “Identity” - Adolphi, Rainer (ETHICS IN PROGRESS, 2021)
The article discusses a central topic of contemporary understandings of society that seems to have no place in Hegel’s theory: the topic of “identity”, which seems to fall between the process of a “struggle for recognition” on the one hand, and, on the other, a consolidated recognition of subjects and their rights within the established social order. The article would like to propose a further reconstruction here. It discusses which considerations should be included so that the discourse on “identity” does not end in any substantialist or ethno-national, egocentric understandings, but, instead, could become possibly a part of Hegel’s theory. In today’s dynamics and unsettling changes, there are undeniable needs for “identity” (which are also easily addressed, even fuelled, by corresponding offers). These are, as one could learn from Hegel, surrogates of a still not or no longer successful sufficient recognition. In this, “identity” is to be understood as critical work on oneself as a product of becoming, on inheritances, achievements, challenges, divisions, discrepancies, guilt and failures.